Pinpointing Cancer Sub-Type Specific Metabolic Tasks Facilitates Identification of Anti-cancer Targets - Gao, Shuaishi; Dai, Ziwei; Xu, Hanyu; Lai, Luhua (Frontiers in Medicine, 2022)
Metabolic reprogramming is one of the hallmarks of tumorigenesis. Understanding the metabolic changes in cancer cells may provide attractive therapeutic targets and new strategies for cancer therapy. The metabolic states are not the same in different cancer types or subtypes, even within the same sample of solid tumors. In order to understand the heterogeneity of cancer cells, we used the Pareto tasks inference method to analyze the metabolic tasks of different cancers, including breast cancer, lung cancer, digestive organ cancer, digestive tract cancer, and reproductive cancer. We found that cancer subtypes have different propensities towards metabolic tasks, and the biological significance of these metabolic tasks also varies greatly. Normal cells treat metabolic tasks uniformly, while different cancer cells focus on different pathways. We then integrated the metabolic tasks into the multi-objective genome-scale metabolic network model, which shows higher accuracy in the in-silico prediction of cell states after gene knockout than the conventional biomass maximization model. We further implemented the multi-objective genome-scale metabolic network model to predict synthetic lethal target pairs (SLPs) of the Basal and Luminal B subtypes of breast cancer and demonstrated that mitochondrial enzymes are potential targets for drug combinations. We found that patients with higher survival probability have less activated SLPs and the number of activated SLPs can be used as an indicator of relapse free survival. Our study quantitatively analyzes the metabolic tasks of cancer and establishes cancer type-specific metabolic models, which opens a new window for the development of specific anti-cancer drugs and provides promising treatment plans for specific cancer subtypes.